SPECIFIC ISSUES OF PROVIDING INTERNATIONAL FINANCIAL ASSISTANCE TO CHILDREN WHO HAVE SUFFERED IN WAR: WORLD EXPERIENCE - Ustynova, Iryna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of this study is a comprehensive study of the regulatory and legal support for the mechanisms for providing financial assistance to children of Ukraine affected by the war by international partner programs. Research methods: the study was conducted using a system of general scientific and special scientific methods of cognition that provide an objective analysis of the subject under study. When studying this aspect, objectivity, value and structural-system approaches are important, as well as the use of logical techniques, in particular analysis and synthesis, comparison, generalization. Results: key basic components for the implementation of financial assistance to children affected by the armed conflict were identified, taking into account world experience. Discussion: the current state and features of the implementation of financial assistance to persons affected by the armed conflict made it possible to identify relevant mechanisms and programs operating in Ukraine, in particular in terms of assistance to children, proposals were made to regulate such issues as a component in research in financial law.